American visions of Europe Franklin D. Roosevelt, George F. Kennan, and Dean G. Acheson - Harper, John L. 1925-2009 (Cambridge Univ. Press, 1994)
Three learned and elegantly written portraits are set against the background of the dramatic events and foreign policy controversies of the twentieth century. Using a remarkably wide range of sources - including memoirs, original documents, and contemporary fiction - Harper describes how direct experience of Europe and Europeans helped to shape the feelings and attitudes of the three subjects, while providing a sophisticated and subtle analysis of the political and cultural influences that made up the mature vision of each. The seemingly eternal European Question shows few signs of diminishing in importance during the final, post-cold war years of the century. The book's conclusion shows the postwar resonance of the three visions and the way in which they retain their power to influence future U.S. policy toward the Old World